Teologi Belas Kasih dalam Matius 9:13 dan Perspektif Etika Deontologis Kant Bagi Moralitas Sosial - Bachtiar Ari Wicaksono; verry willyam; Ken Jack Gunawan Waoma (STT INTI Bandung, 2025)
Immanuel Kant's deontological ethics emphasizes the significance of the moral foundation underlying actions, rather than morality itself, as a more fundamental and essential element. This approach focuses on the duty to act according to principles (maxims), where the assessment of right or wrong is based on intentions rather than consequences. Kant's categorical imperative underscores that moral actions performed with good intentions inherently bring intrinsic moral value. This study employs a literature review method to examine deontological ethics theory and its connection with Matthew 9:13, which highlights compassion as God's primary desire over sacrifices. Compassion is identified as the motivation that should underpin the fulfillment of moral duties in Christianity, independent of outcomes or consequences. This study aims to provide a rational and objective foundation for moral awareness and ethical principles in Christian life. Specifically, it emphasizes the application of compassion in humanity and religious moderation, stressing the importance of sincere intentions and motivations in fulfilling moral obligations without being influenced by pragmatic objectives